Examining the role of urgency in predicting binge size in bulimia nervosa - Davis, Heather A.; Smith, Gregory T. (Frontiers in Psychology, 2023)
Greater binge size within bulimia nervosa is associated with elevated distress and impairment. Theoretical models posit that emotion dysregulation predicts binge eating, but little research has investigated the potential for dispositional traits that reflect difficulty in emotion regulation to predict binge size among women with bulimia nervosa. Research supports that negative urgency, the tendency to act rashly when feeling distressed, is associated with binge eating behavior among individuals with bulimia nervosa. Relatively fewer studies have explored associations between binge eating and positive urgency, the tendency to act rashly when feeling extreme positive affect. The urgency traits may predict greater binge size within bulimia nervosa. The current study sought to examine negative urgency and positive urgency as predictors of test meal intake in a sample of 50 women, n = 21 with bulimia nervosa and n = 29 healthy controls. Dispositional levels of positive urgency, negative urgency, positive affect, and negative affect were measured prior to a laboratory binge eating paradigm. Participants in the bulimia nervosa group scored higher on negative urgency, positive urgency, and negative affect than participants in the control group. Across participants, lower levels of negative affect were associated with greater test meal intake. Elevated levels of positive urgency predicted significantly greater test meal intake, but only for participants with bulimia nervosa. No other dispositional traits predicted test meal intake when the interaction of positive urgency and group was included in the model. Findings suggest positive urgency is an underappreciated, but potentially important, risk factor for greater binge size in bulimia nervosa.